Revealing the interactions between pentagon–octagon–pentagon defect graphene and organic donor/acceptor molecules: a theoretical study1. Issue 7 (21st February 2015) - Li, Jie-Wei; Liu, Yu-Yu; Xie, Ling-Hai; Shang, Jing-Zhi; Qian, Yan; Yi, Ming-Dong; Yu, Ting; Huang, Wei
<x xml:space="preserve">Abstract</x> The cyano group interacts strongly with 5–8–5 defect graphene, changes the bands near the Fermi level and enhances the infrared light absorption.